Latent growth curve modeling of psychological well-being trajectories - Salgueiro, M.F.; Malta, J. (American Journal of Theoretical and Applied Statistics, 2013)
This Paper Proposes Modeling Trajectories of Psychological Well-being Using Latent Growth Curve models (LGCMs). The psychometric scale of the General Health Questionnaire-12 (GHQ-12) is considered. Data from the British Household Panel Survey (BHPS), from years 2003 to 2006 are used. In 1991 Graetz proposed the GHQ-12 as a multidimensional scale, containing three distinct dimensions: anxiety and depression, social dysfunction and loss of confidence. Using such scale, this paper compares a second-order LGCM for the trajectories of a latent factor (measured by these three dimensions) with a LGCM for the trajectories of an overall sum score. Conditional LGCMs are then fitted; sex, age group and perceived health status are considered as the explanatory variables of the growth trajectories. Results show that the model which considers the three dimensions of subjective well-being has a larger explaining capability than the one utilizing the subjective well-being score.